Diabetes, Biochemical Markers of Bone Turnover, Diabetes Control, and Bone - Starup-Linde, Jakob (Frontiers in Endocrinology, 2013)
Diabetes mellitus is known to have late complications including micro vascular and macro vascular disease. This review focuses on another possible area of complication regarding diabetes; bone. Diabetes may affect bone via bone structure, bone density and biochemical markers of bone turnover. The aim of the present review is to examine in vivo from humans on biochemical markers of bone turnover in diabetics compared to non-diabetics. Furthermore, the effect of glycemic control on bone markers and the similarities and differences of type 1- and type 2- diabetics regarding bone markers will be evaluated. A systematic literature search was conducted using Pubmed, Embase, Cinahl and Svemed+ with the search terms: “Diabetes mellitus”, “Diabetes mellitus type 1”, “Insulin dependent diabetes mellitus”, “Diabetes mellitus type 2”, “Non insulin dependent diabetes mellitus”, “Bone”, “Bone and Bones”, “Bone diseases”, “Bone turnover”, “Hemoglobin A Glycosylated and “HbA1C”. After removing duplicates from this search 1,188 records were screened by title and abstract and 75 records were assessed by full text for inclusion in the review. In the end 43 records were chosen. Bone formation and resorption markers are investigated as well as bone regulating systems. T1D is found to have lower osteocalcin and CTX, while osteocalcin and tartrate resistant acid are found to be lower in T2D, and sclerostin is increased and collagen turnover markers altered. Other bone turnover markers do not seem to be altered in T1D or T2D. A major problem is the lack of histomorphometric studies in humans linking changes in turnover markers to actual changes in bone turnover and further research is needed to strengthen this link.